2012
DOI: 10.1016/j.socscimed.2012.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based violence and HIV sexual risk behavior: Alcohol use and mental health problems as mediators among women in drinking venues, Cape Town

Abstract: Gender-based violence is a key determinant of HIV infection among women in South Africa as elsewhere. However, research has not examined potential mediating processes to explain the link between experiencing abuse and engaging in HIV sexual risk behavior. Previous studies suggest that alcohol use and mental health problems may explain how gender-based violence predicts sexual risk. In a prospective study, we examined whether lifetime history of gender-based violence indirectly affects future sexual risk behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 43 publications
4
59
0
Order By: Relevance
“…In addition, sexual risk behaviour (having had two or more sexual partners in the past year) and having a history of an STI in bivariate analysis was found to be associated with IPV. Similar results were found in previous studies [32][33][34] . Alcohol use in the context of sexual activity may reduce the ability to avoid violence 17,51 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, sexual risk behaviour (having had two or more sexual partners in the past year) and having a history of an STI in bivariate analysis was found to be associated with IPV. Similar results were found in previous studies [32][33][34] . Alcohol use in the context of sexual activity may reduce the ability to avoid violence 17,51 .…”
Section: Discussionsupporting
confidence: 93%
“…Sociodemographic factors for IPV among university students may include, female gender (although some report similar proportions of IPV between females and males) 16,20,24,25 earlier year of study 18 being single 17,19 and residing in a campus residence 19 . Individual risk factors for IPV may include childhood physical or sexual abuse or other prior victimization as well as history of interparental violence 17,18,25,26 substance use (alcohol and tobacco use) 17,[27][28][29] posttraumatic stress disorder (PTSD), depression, and suicidal behaviour 14,16,24,30,31 and sexual risk behaviour, including sexually transmitted infections (STI) and HIV [32][33][34] . Protective factors may include lack of peer and parental social support 22 lack of life satisfaction 20,24 high religiosity 35 low perceived control 36 lower Gross national income but not family income 37 .…”
Section: African Journal Of Reproductive Health March 2016; 20 (1): 30mentioning
confidence: 99%
“…[8] Conversely, research indicates that women with mental health problems, particularly comorbid drinking and substance use problems, are at heightened risk for HIV, primarily as a result of high sexual risk-taking behaviour. [9] Common mental disorders compromise quality of life and functional outcomes in HIV-positive individuals. [5] Furthermore, traumatic stress, or exposure to traumatic events/situations, whereby individuals are overwhelmed by an inability to cope with the experience, accelerates disease progression in HIV-infected individuals by suppressing immune functioning.…”
Section: The Golden Thread: a Focus On Mental Healthmentioning
confidence: 99%
“…Studies have shown that women who have been subjected to GBV often adopt risky behaviors such as alcohol abuse, which in turn can lead to more unprotected sex and an increased risk of acquiring HIV. [23][24][25] The fear of IPV can also discourage women from getting tested for HIV, [26] discourage disclosure of their HIV-positive status [27] and serve as a barrier to treatment uptake and adherence, [27,28] and may disrupt HIV prevention services [29] and result in poorer HIV outcomes. [28,30] The relationship between IPV and HIV is also bidirectional.…”
Section: Guest Editorialmentioning
confidence: 99%